2019
DOI: 10.1186/s12885-019-6244-6
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic impact of GSTM1/GSTP1 genetic variants in bladder Cancer

Abstract: BackgroundThe glutathione S-transferases (GSTs) are a superfamily of phase II detoxifying enzymes that inactivates a wide variety of potential carcinogens through glutathione conjugation. Polymorphic changes in the GST genes have been reported to be associated with increased susceptibility to cancer development and anticancer drug resistance. In this study, we investigated the association between genetic variants in GSTM1 and GSTP1 and patients’ clinicopathological parameters. The prognostic values of such ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…It is well-known that certain GSTs classes, namely a, μ and π, are involved in the development of anti-cancer drug-resistance phenomena [ 11 ]. For example, GSTA1-1 and GSTP1-1 were reported to be, in short, connected with an increased risk of gastric, breast and pancreatic cancer [ 1 , 12 , 13 , 14 , 15 , 16 ]. Moreover, the isoenzyme GSTM1-1 is mostly studied in humans for its correlation with many types of cancer [ 13 , 14 , 15 ], while other studies support its pertinence with Parkinson’s disease [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well-known that certain GSTs classes, namely a, μ and π, are involved in the development of anti-cancer drug-resistance phenomena [ 11 ]. For example, GSTA1-1 and GSTP1-1 were reported to be, in short, connected with an increased risk of gastric, breast and pancreatic cancer [ 1 , 12 , 13 , 14 , 15 , 16 ]. Moreover, the isoenzyme GSTM1-1 is mostly studied in humans for its correlation with many types of cancer [ 13 , 14 , 15 ], while other studies support its pertinence with Parkinson’s disease [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, GSTA1-1 and GSTP1-1 were reported to be, in short, connected with an increased risk of gastric, breast and pancreatic cancer [ 1 , 12 , 13 , 14 , 15 , 16 ]. Moreover, the isoenzyme GSTM1-1 is mostly studied in humans for its correlation with many types of cancer [ 13 , 14 , 15 ], while other studies support its pertinence with Parkinson’s disease [ 17 , 18 ]. Many studies have shown that an overexpression of GSTM1-1 may have direct impact on chemoresistance [ 13 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bladder cancer, the ninth most common cancer worldwide, is a highly heterogeneous disease and an important cause of cancer metastasis-related death. 1 In the United States, it has been estimated that there would be about 80,470 new bladder cancer cases and 17,670 deaths in 2019. 2 The incidence of bladder cancer is higher in males and 70% of patients with bladder cancer are initially diagnosed as non-muscular invasive diseases.…”
Section: Introductionmentioning
confidence: 99%
“…There are several risk factors related to bladder cancer, such as smoking, aging and exposure to the products of chemical industries. 1 , 3 In recent years, despite the progress in clinical diagnosis and treatment of bladder cancer, it remains to be a perplexing problem in clinical management due to its high metastasis rate. 4 Therefore, a comprehensive understanding of the pathogenetic mechanism of bladder cancer would improve the prognosis of patients.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been demonstrated that DOCK2 was abnormally elevated expressed in B-cell lymphoma and the overexpressed DOCK2 correlated with the reduced prognosis of chronic lymphocytic leukaemia 40,41. GSTM1 (glutathione S-transferase M1) is a member of the family of cytosolic GSTs, and the null genotype of GSTM1 has been proven to be associated with risk of colorectal cancer, renal cell carcinoma, oesophageal cancer, nasopharyngeal cancer and bladder cancer [42][43][44][45][46]. LAPTM5 (lysosomal-associated protein transmembrane 5) is a membrane protein that can inhibit the expression of T-cell receptor (TCR) and play a positive role in migration and invasion of ovarian cancer cell but play a negative regulator of T-cell or B-cell receptor downstream signalling.…”
mentioning
confidence: 99%